Levers in removable dental prostheses - A. Monzavi; R Mosharaf (Tehran University of Medical Sciences, 1997)
Teeth and periodontal ligaments can resist more efficiently opposing vertical forces parallel to their axial axis in comparison to horizontal forces. Thus, in designing dental prostheses and preserving interocclusal relationships we should notice to eliminate horizontal forces on teeth. A partial prosthesis can rotate in vertical, horizontal and Sagittal axis and by understanding levers and designing appropriate frameworks these rotations can be avoided.